Anodization Of Titania Nanotube Arrays In Electrolyte Ontaining Hydrogen Peroxide - Lee, Kar Chun (2018)
It is well-accepted that anodization conducted in H2O2 as oxidant could facilitate rapid growth of nanotube for photocatalyst application. However, the corrosion behaviour, formation mechanism of compact oxide layer and nanotube associated with anodization in electrolyte containing H2O2 remains unanswered. Therefore, anodization of titania nanotube (TNT) in H2O2-based electrolyte are studied relative to H2O for better understanding on the formation of TNT nanotube as well as the formation of its surface oxide layer. Besides, the study aimed to explore the by product in anodic waste electrolyte for chemical recycling of Ti4+ species. Two-electrode anodization is conducted at 60 V for 1 hour by connecting the Ti and Pt foils to positive and negative terminal respectively using ethylene glycol, ammonium fluoride and different oxidants (H2O and H2O2) as electrolyte. Based on the current-time transient profiles, it is well-verified that the presence of •OOH and OOH- species facilitate stronger electrochemical reactions on substrate surface. It is found that presence of Ti4+(H2O2) species in the electrolyte raises the electrolyte temperature up to 55 °C, promoting the fluoride activity and leading to corrosion of substrate. Under similar temperature profile, sample anodized in H2O experiences a more severe corrosion. The observation fulfils the expectance where H2O2 species demonstrates a stronger passivation tendency. The investigation on the origin of compact oxide was made based on the nanotube-splitting model and initiation model. The formation of compact oxide layer can be more accurately described by initiation layer model. On this premise, it is suggested that nanotube is grown at the metalmetal oxide interface. Experimental works on single-sided (SA) vs double sided anodization (DA) configuration showed that SA produces a thick wall nanotube array which exhibits a much higher and stable photocurrent of 1.6 mA cm-2 at 0 V. Based on the morphology changes observed, formation mechanism of nanotube is greatly influenced by the compact oxide layer present above. Therefore, the compact oxide formation must be taken into consideration when devising nanotube growth model. Besides, the post-anodized electrolyte is filtered, dried and characterized. The byproduct extracted from waste anodic electrolyte was identified as (NH4)3TiOF5, with highly symmetrical F(m3m) octahedral structure. Annealing at 200 °C decomposes the yellowish powder, (NH4)3TiOF5 into (NH4)TiOF3 and (NH4)2TiF6.